Performance Assessment of a Floating Photovoltaic Powerplant in Iran: A Case Study on Amir Kabir Dam, Karaj - Maryam Karami; Mojtaba Azhdari Khameneh (Journal of Heat and Mass Transfer Research)
In this study, a floating photovoltaic power plant (FPVPP) on the Amir Kabir dam in Karaj, Iran is designed and optimized in terms of energy, economic, and environmental analysis. The FPVPP is designed to supply the power needs of Varian village, which is located near the Amir Kabir dam. The results showed that under the same climatic conditions, the operating temperature of the panels of the ground-mounted PVPP is 4.7℃ higher than that of the floating PVPP, and the output voltage and power of the floating PVPP are 5.7 V and 2.05 kW higher than that of the ground-mounted one, respectively. The floating PVPP provides approximately 69.4% of the annual power needs of the Varian village. The average daily output of the floating PVPP is 280 kWh/day, which meets the daily needs of the village. The payback time is 9.88 years, 3.59 years, and 7.47 years by considering the electricity cost in Iran with subsidy and without subsidy and the electricity cost in the United States, respectively. The designed floating PVPP saves 488 m2 of land and a total of about 260,000 m3 of water is directly and indirectly saved. This floating PVPP can prevent the emission of 22768 kg/year of carbon dioxide, 99 kg/year of sulfur dioxide, and 48 kg/year of nitrogen oxide.